Maxwell's Flame - Trow M. J. (New English library)
Forced to attend a GNVQ course in Kent, schoolteacher Peter Maxwell finds himself embroiled in murder when one of the teachers is battered to death. When the second victim is one of Maxwells old flames, it becomes more personal, and when Max takes something personally, he gets results.